Fides Quaerens Corporalitatem: Perspectives on liturgical embodiment - Cilliers, Johan (Verbum et ecclesia, 2009)
In the light of a number of paradigm shifts that have taken place in practical theological methodology, this article proposes an integrative approach that takes the fundamental role of embodiment into account. A brief discussion of the theological understanding of embodiment is followed by a reflection on certain liturgical implications, inter alia liturgical embodiment as immediate participation; as multi-sensory interpretative act; and as broken presence and celebrated absence.